Job satisfaction among e-PJJ degree nursing students at UiTM Puncak Alam Campus / Roslinda Isa, Che Wan Kasmiza Che Wan Ahmad and Siti Katijah Yahya - Isa, Roslinda; Che Wan Kasmiza, Che Wan Ahmad; Yahya, Siti Katijah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Job satisfaction is defined as the extent to which an employee feels self-motivated, content and satisfied with nurses’ job and is an exciting issue discussed in every fields of career including in nursing profession. A satisfied employee is always important for an organization as they aim to deliver the best of their capability. This study was to determine the level of job satisfaction, level of workload and whether the workload is significant to affect the job satisfaction among e-PJJ degree nursing students.This study used descriptive cross-sectional study with a probability sampling among 90 e-PJJ degree nursing students in UiTM, Puncak Alam Campus, Selangor Darul Ehsan. The instruments were McCloskey/Mueller Satisfaction Scale (MMSS) containing 31 questions and NASA Task Load Index containing seven questions. Results for job satisfaction level and workload level were moderate-high among all respondents involved. Data analysis shows moderate high level of workload and job satisfaction, which indicates the sample was not affected by most jobs given when fulfill their responsibility as a registered staff nurse.The correlation between job satisfaction among e-PJJ